Gross Anatomical Studies on the Thyroid Gland of Male and Female Chabro Chicken Reared during Summer Season - Vishen, Amit Singh (Indian Journal of Veterinary Anatomy, 2019)
Gross anatomical studies were conducted on thyroid gland of eight weeks- old 12 apparently healthy Chabro chickens (six males and six females) reared in summer season. The thyroid glands appeared as light pink coloured oval bodies i.e. right and left glands located on the ventral surface of the base of the neck just caudal to the junction of subclavian and common carotid arteries. The left thyroid gland was situated more cranially than the right one. Average weight of the thyroid gland in males was higher (0.091±0.03 gm) than females (0.078±0.004 gm). The average length and width were less in females than the males. The average thickness of the thyroid gland was more in females (3.106±0.188 mm) than males (2.818±0.05 mm). The difference in biometrical parameters in male and female Chabro chicken in summer season was due to effect of sex hormones and feeding behaviour.